Pendampingan, Pelatihan dan Implementasi Digital Marketing pada Masyarakat Desa Lubuk Nipis, Kecamatan Panang Enim, Kab. Muara Enim - Muhajir Arafat; Suryanto Suryanto; Rusidi Rusidi; M As'ad; Dian Sri agustina; Yunita Trimarsiah; Satria Novari; Dodi Herryanto; Taufik Saobri (Jurnal Pengabdian Masyarakat (ABDIRA), 2023)
Lubuk Nipis Village, Panang Enim District, Muara Enim Regency, has the potential for various tourism and handicraft products in the form of culinary as well as in the form of handicraft objects and so on. Management of the tourism sector and MSMEs in Lubuk Nipis village is starting to become a concern in Muara Enim district. As a pilot tourism village, innovation is needed in promoting tourist attractions, the results of MSMEs in Lubuk Nipis village to the wider community. This community service activity focuses on training and helping promote tourism and the results of MSMEs in the Lubuk Nipis village community. This PKM activity will provide training in the form of creating promotional content that will be disseminated through social media such as Facebook, Instagram, TikTok and Youtube.